A population-based study of 135 lymphomas after solid organ transplantation: The role of Epstein-Barr virus, hepatitis C and diffuse large B-cell lymphoma subtype in clinical presentation and survival. (May 2014) - Kinch, Amelie; Baecklund, Eva; Backlin, Carin; Ekman, Tor; Molin, Daniel; Tufveson, Gunnar; Fernberg, Pia; Sundström, Christer; Pauksens, Karlis; Enblad, Gunilla
Abstract Background. Epstein-Barr virus (EBV) plays a major role in the development of post-transplant lymphoproliferative disorder (PTLD), but there is an increasing awareness of EBV-negative PTLD. The clinical presentation of EBV-negative PTLD has not been as well characterised as EBV-positive cases. Further, there is limited knowledge on the clinical importance of diffuse large B-cell lymphoma (DLBCL) cell of origin subtype post-transplant. Materials and methods. We studied the role of EBV, hepatitis C (HCV) and DLBCL subtype in clinical presentation and survival in 135 post-transplant lymphomas diagnosed 1980–2006 in a population-based cohort of 10 010 Swedish solid organ transplant recipients. The lymphomas were re-evaluated according to WHO 2008, examined for EBV, and clinical data were collected from medical records. Results. Lymphoma incidence rate was 159/100 000 person-years and is also reported by lymphoma subtype. EBV-negative lymphomas constituted 48% and were associated with HCV infection (p = 0.02), bone marrow involvement (p < 0.001), and T-cell phenotype (p = 0.002). Among DLBCL, 78% were of non-germinal centre subtype, which was associated with EBV-positivity (69%, p = 0.001), early occurrence (p = 0.03), heart/liver/lung/pancreas recipients (p = 0.02), anti-T-cell globulin (p = 0.001), and tacrolimus treatment (p = 0.02). DLBCL subtypes had similar overall survival. Five-year overall survival was 42% in all treated patients. Independent poor prognostic factors were older age, B symptoms, ECOG 2-4, kidney/pancreas/heart recipients, T-cell lymphoma, and HCV-infection. Conclusions. With long follow-up, a large part of PTLD is EBV-negative, due to a high proportion of T-cell lymphomas and low of polymorphic PTLD. EBV-negative PTLD have a different clinical presentation. HCV may play an aetiological role in late-onset PTLD and was revealed as a new prognostic factor for inferior survival that needs to be confirmed in larger studies. The heavier immunosuppression in non-kidney transplantations seems to play a role in the development of non-germinal centre DLBCL. DLBCL cell of origin subtype lacks prognostic importance in the transplant setting.